Energy requirement assessment in Japanese table tennis players using the doubly labeled water method - Sagayama, H.; Hamaguchi, G.; Toguchi, M.; Ichikawa, M.; Yamada, Y.; Ebine, N.; Higaki, Y.; Tanaka, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Total daily energy expenditure (TEE) and physical activity level (PAL) are important for adequate nutritional management in athletes. The PAL of table tennis has been estimated to about 2.0: it is categorized as a moderateactivity sport (4.0 metabolic equivalents [METs]) in the Compendium of Physical Activities. However, modern table tennis makes high physiological demands. The aims of the current study were to examine (1) TEE and PAL of competitive table tennis players and (2) the physiological demands of various types of table tennis practice. In Experiment 1, we measured TEE and PAL in 10 Japanese college competitive table tennis players (aged 19.9 ± 1.1 years) using the doubly labeled water (DLW) method during training and with an exercise training log and self-reported energy intake. TEE was 15.5 ± 1.9 MJ·day-1 (3695 ± 449 kcal·day-1); PAL was 2.53 ± 0.25; and the average training duration was 181 ± 38 min·day-1. In Experiment 2, we measured METs of five different practices in seven college competition players (20.6 ± 1.2 years). Three practices without footwork were 4.5-5.2 METs, and two practices with footwork were 9.5-11.5 METs. Table tennis practices averaged 7.1 ± 3.2 METS demonstrating similarities with other vigorous racket sports. In conclusion the current Compendium of Physical Activities underestimates the physiological demands of table tennis practice for competition; the estimated energy requirement should be based on DLW method data.